Directing agricultural research forward alternative development. (1996)
Discusses the IICA/GTZ project to provide an alternative form of development for the Amazon region of Peru and the other Andean countries. The objective of the project is to support sustainable agricultural development in areas ewhere there is widespread cultivation of illicit crops such as the coco leaf, and to do so with the active participation of agricultural research institutions.
DC